Introduction to linear regression analysis - Montgomery, Douglas C.; Peck, Elizabeth A., 1953; Vining, G. Geoffrey 1954 (Wiley series in probability and statistics, 2020)
"In statistics, linear regression is a linear approach to modelling the relationship between a scalar response and one or more explanatory variables. A linear regression model attempts to explain the relationship between two or more variables using a straight line."--